The Impact of Dignity Therapy on Psychological Well-Being and Quality of Life in Terminally Ill Cancer Patients: A Systematic Review - PRIBADI, DIMAS RIA ANGGA; Fauzi, Ekan; Wibowo, Thomas Ari (STIKes Hamzar, 2025)
Dignity therapy (DT) aims to enhance the dignity, meaning, and emotional well-being of terminally ill cancer patients. While research investigates DT’s application in palliative care, a comprehensive systematic review synthesizing its effects remains lacking. Objective: This systematic review assesses the efficacy of DT in improving psychological and existential outcomes for terminally ill cancer patients. Methods: A systematic review adhering to the PRISMA guidelines was conducted. Searches across Medline, PubMed, Scopus, and CINAHL databases yielded 113 references, which were screened against 10 studies meeting inclusion criteria. Results: DT demonstrates positive effects on dignity, sense of purpose, meaning in life, and hope. However, its impact on psychosocial distress, particularly depression and anxiety, is inconclusive. DT’s acceptance rate was high, with over 80% of participants reporting satisfaction. Quality of life improvements varied, with some significant enhancements and others exhibiting minimal impact. Conclusion: DT is a feasible intervention that offers psychosocial benefits for terminally ill cancer patients in palliative care settings.It enhances dignity, facilitates family communication, and offers existential relief. Further research is necessary to standardize protocols, conduct long-term follow-ups, and integrate DT into interdisciplinary palliative care models.